Study of effect of glycemic control on haemoglobin levels in patients with type 2 diabetes mellitus - G., Aishhwarrya Umeshchandara; K., Ravi (International Journal of Advances in Medicine, 2020)
Background: Anemia is more frequent and severe in diabetics compared to non-diabetic patients. Chronic anemia results in tissue hypoxia, which is known to play a key role in diabetes-associated organ damage. Hence it is important to diagnose and correct anemia in diabetic patients. This study was done to elucidate the effect of glycemic control on haemoglobin levels in patients with type 2 Diabetes mellitus. Methods: The present study is an observational, cross sectional study conducted between November 2017 to May 2019 carried out in hospitals attached to Bangalore Medical college and Research Institute. A sample of 60 patients with Diabetes mellitus were included, out of which 28 were female and 32 were male patients. Results: Study was conducted on 60 patients, the age distribution was between 29yrs to 88yrs with mean age was 56±11yrs. Out of 60 patients 23 patients had anemia. There was slight positive correlation between haemoglobin percentage and HbA1c. But this was not statistically significant. Conclusions: The study concludes that Glycemic control was not found to influence the Haemoglobin levels in patients with Type 2 diabetes mellitus in a significant manner. In subjects with anemia, multiple other issues need to be addressed for improvement in haematocrit value and prevention of complications of diabetes apart from glycemic control.